The Pilates powerhouse : the essential home guide for improving strength, tone, shape and balance - Winsor, Mari; Laska, Mark (London : Vermilion, 1999)
Demonstrates a program of mat exercises that follows the Pilates philosophy of low-stress conditioning.
Part 1 The Power of Pilates -- Part 2 Doing It -- Part 3 Injuries and Injury Prevention.
Keywords: Exercise; Stretching exercises; Physical fitness